Influence of Toposequence on Physical and Mineralogical Properties of Soils Developed on Basaltic Parent Material under Sub-humid Terrestrial Ecosystem - Tülay Tunçay; Orhan Dengiz; Ali İmamoğlu (Journal of Agricultural Sciences, 2020)
Understanding of soil forming factors is crucial to define physical, mineralogical and morphological properties of soils. In addition to that soil formations were highly associated with slope positions which have influence on pedogenetic and weathering process of the soils. Because, topography or relief affects how water and other material are added to and removed from soils. The aim of this study is to enhance our understanding of the role toposequence in controlling chemical weathering, influence on physical and mineralogical properties in soils developed on basaltic parent material under sub-humid terrestrial ecosystem in Black Sea region of Turkey using geochemical and mineralogical data obtained from X-ray diffraction and Scanning Electron Microscope analysis. For this purpose, four representative profiles formed on different topographic positions of transect were investigated and designated according to Soil Survey Staff (2014)/IUSS Working Group WRB (2015) classification systems. The results clearly showed that topography strongly affects soil physical, mineralogical and morphological characteristics either directly or indirectly in the local region even soils formed on the same parent material with the same climatic condition. This case was also explained with chemical weathering indices (Chemical Index of Alteration and Chemical Index of Weathering) in this study.